Capital Flows with Debt- and Equity-Financed Investment-Equilibrium Structure and Efficiency Implications - Razin, Assaf; Sadka, Efraim; Yuen, Chi-Wa. (Washington, D.C. : International Monetary Fund, 1998)
This paper distinguishes between debt and equity flows in the presence of information asymmetry between the firm's 'insiders' and 'outsiders' in a small open economy. It shows the inadequacy of capital investment because its scope is too narrow and the investment each firm makes is too little. An unconventional policy tool is proposed to correct the market failure: lump-sum subsidies to firms that choose to equity-finance their investments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet